Enhancement of Shiga Toxin Production in Enterohemorrhagic Escherichia coli Serotype O157:H7 by DNase Colicins - Toshima, Hirono (American Society for Microbiology (ASM), 2007)
Colicins are proteins produced by and active against several strains of Escherichia coli. Previously we reported that colicinogenic bacteria seemed beneficial in preventing the clinical manifestations of infectious disease caused by enterohemorrhagic E. coli O157 in humans. The inhibitory effects could be due to a decrease in O157 levels and/or pathogenicity. This study investigated the effects of colicinogenic E. coli on the production of Shiga toxin (Stx) by O157. Standard strains of colicinogenic bacteria carrying plasmids for each type of colicin (E3/5/8/9) were used for the study. The O157 strains were cultured in the presence of colicinogenic bacteria or extracted colicins. Compared with results for controls, DNase colicins (E8/9) facilitated an 8- to 64-fold increase in production of Stx2, while RNase colicins (E3/5) suppressed Stx production in only two strains. Stx prophages were induced in synchrony with Stx production. Semiquantitative real-time reverse transcription-PCR (RT-PCR) was then performed to examine SOS gene expression. The RT-PCR results clearly indicated a marked increase in mRNA levels of SOS reaction-associated genes after the addition of DNase colicins. We believe that Stx prophages are induced by the SOS response to DNA damage caused by DNase colicins, thus leading to higher Stx production. These findings suggest that while colicinogenic bacteria can be antagonistic to O157 infection, DNase colicins may enhance Stx production. Thus, colicinogenic flora is likely to be involved in the complex pathogenic pathways of O157 infection, and further investigation should be performed before the use of colicinogenic bacteria as an intervention method.